Technological optimization of manufacture of probiotic whey cheese matrices - Madureira, Ana R. (2012)
In attempts to optimize their manufacture, whey cheese matrices obtained via thermal processing of whey (leading to protein precipitation) and inoculated with probiotic cultures were tested. A central composite, face-centered design was followed, so a total of 16 experiments were run using fractional addition of bovine milk to feedstock whey, homogenization time, and storage time of whey cheese as processing parameters. Probiotic whey cheese matrices were inoculated with Lactobacillus casei LAFTIR L26 at 10% (v/v), whereas control whey cheese matrices were added with skim milk previously acidified with lactic acid to the same level. All whey cheeses were stored at 7 ◦C up to 14 d. Chemical and sensory analyses were carried out for all samples, as well as rheological characterization by oscillatory viscometry and textural profiling. As expected, differences were found between control and probiotic matrices: fractional addition of milk and storage time were the factors accounting for the most important effects. Estimation of the best operating parameters was via response surface analysis: milk addition at a rate of 10% to 15% (v/v), and homogenization for 5 min led to the best probiotic whey cheeses in terms of texture and organoleptic properties, whereas the best time for consumption was found to be by 9 d of storage following manufacture.